MRJF4, a novel histone deacetylase inhibitor, induces p21 mediated autophagy in PC3 prostate cancer cells - Di Giacomo, V; Di Valerio, V; Rapino, M; Bosco, D; Cacciatore, I; Ciulla, M; Marrazzo, A; Fiorito, J; Di Stefano, A; Cataldi, A (Cellular and Molecular Biology, 2015)
Autophagy is a cellular defense mechanism which occurs through degradation and recycling of cytoplasmic constituents and represents a caspase-independent alternative to cell death by apoptosis. It is generally accepted that the suppression of autophagy in many cancer cells is directly correlated to malignancy; hence, the control of autophagy genes could represent a target for cancer therapy. The inhibition of cell proliferation through autophagy activation could be an important mechanism for many anti-tumor drugs. Here we report the effects of a novel histone deacetylase inhibitor MRJF4 (racemic mixture) and of its two enantiomers [(+)-MRJF4 and (-)-MRJF4] on the morphological and molecular mechanisms causing death and migration of PC3 prostatic cancer cells. In particular, we investigated the occurrence of the autophagic process, both at morphological and molecular levels (LC3 expression), and its relationship with p21, a key molecule which regulates cell cycle and autophagy cell death. Moreover, pERK/Nf-kB driven intracellular signaling, the expression of MMP9 protein - a key component of cell migration - invasion, and metastasis were assayed. Our results showed that the anti-proliferative effects of MRJF4 due to autophagy occurrence, documented by LC3 increase and ultrastructural modifications, and the reduction of invasiveness seem to be mediated by the down-regulation of pERK/NF-kB signaling pathway, along with p21 up-regulation.